Behind the gas mask : the U.S. Chemical Warfare Service in war and peace - Faith, Thomas I., 1979- (University of Illinois Press, 2014)
This work offers an institutional history of the Chemical Warfare Service (CWS), the department tasked with improving the Army's ability to use and defend against chemical weapons during and after World War I.